Ceftazidime‐Avibactam Population Pharmacokinetic Modeling and Pharmacodynamic Target Attainment Across Adult Indications and Patient Subgroups. Issue 2 (28th September 2018) - Li, Jianguo; Lovern, Mark; Green, Michelle L.; Chiu, Joannellyn; Zhou, Diansong; Comisar, Craig; Xiong, Yuan; Hing, Jeremy; MacPherson, Merran; Wright, James G.; Riccobene, Todd; Carrothers, Timothy J.; et al.
Abstract : Ceftazidime‐avibactam is a novel β‐lactam/β‐lactamase inhibitor combination for the treatment of serious infections caused by resistant gram‐negative pathogens. Population pharmacokinetic (PopPK) models were built to incorporate pharmacokinetic (PK) data from five phase III trials in patients with complicated intra‐abdominal infection (cIAI), complicated urinary tract infection (cUTI), or nosocomial (including ventilator‐associated) pneumonia. Ceftazidime and avibactam pharmacokinetics were well‐described by two‐compartment disposition models, with creatinine clearance (CrCL) the key covariate determining clearance variability. Steady‐state ceftazidime and avibactam exposure for most patient subgroups differed by ≤ 20% vs. healthy volunteers. Probability of PK/pharmacodynamic (PD) target attainment (free plasma ceftazidime > 8 mg/L and avibactam > 1 mg/L for ≥ 50% of dosing interval) was ≥ 94.9% in simulations for all patient subgroups, including indication and renal function categories. No exposure‐microbiological response relationship was identified because target exposures were achieved in almost all patients. These modeling results support the approved ceftazidime‐avibactam dosage regimens (2000‐500 mg every 8 hours, adjusted for CrCL ≤ 50 mL/min).